FORMULATION AND EVALUATION OF TRANSDERMAL PATCH OF INDOMETHACIN CONTAINING PATCHOULI OIL AS NATURAL PENETRATION ENHANCER - Das, Asha; Ahmed, Abdul Baquee (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To develop a transdermal patch of Indomethacin using patchouli oil as a natural enhancer to increase transdermal permeation of the drug from the matrix system across rat epidermis. Materials and Methods: The chemical characterization of patchouli oil was done by gas chromatography-mass spectrometry. Transdermal patches of indomethacin were formulated after studying the drug-excipient compatibility studies by differential scanning calorimetry and Fourier transform infrared spectroscopy (FTIR). The transdermal patches were evaluated for various physiochemical properties. In-vitro transdermal permeation was carried using modified Keshary-Chein diffusion cell across rat epidermis. FTIR studies of rat epidermis were done to understand the mechanism of the permeation enhancing effect of the oil from the matrix patch. Result: The results of physiochemical parameters of the transdermal patch were found satisfactory. The transdermal flux obtained of the different concentration of patchouli oil tend to increase with increasing concentration of the oil and the maximum transdermal flux of 61.92 ± 0.89 μg/cm2/hr was obtained with formulation F7 (containing 1% w/v of patchouli oil) which is similar to the flux of the formulation F2 containing standard enhancer dimethyl sulphoxide. The skin irritation test did not show any edema and the FTIR data of rat epidermis indicated that patchouli oil enhances transdermal permeation of indomethacin by partial extraction of lipids in the stratum corneum. Conclusion: Thus, the results showed a potential enhancing effect of patchouli oil on the transdermal permeation of the model drug indomethacin and may be used as natural permeation enhancer in transdermal drug delivery systems.